State Revenue Policy: Analysis of the Tax System and Non-Tax State Revenue (PNBP) - Risma Mawarni (Journal Arbitrase : Economy, Management and Accounting, 2025)
Non-Tax State Revenue (PNBP) plays a crucial role in fiscal consolidation and economic sustainability. The Indonesian government continues to optimize state revenue through tax reform, natural resource management, and service innovation, with the aim of driving post-pandemic economic recovery. Although the Covid-19 pandemic caused a decline in state revenue performance in 2020, the economic recovery in 2021 has resulted in a significant increase in tax revenue and PNBP. This study uses a literature review method to evaluate the effectiveness of fiscal policy and provide recommendations for improving state revenue management. Tax revenue remains the primary source, while PNBP has experienced an increase influenced by global commodity prices. Targeted fiscal policy and the use of information technology are considered crucial in optimizing state revenue to support fiscal consolidation and economic growth.